Pesticides in use, their application and risks on human health and ecosystems: A case of Fogera District, Ethiopia - Abebaw Abaineh; Dessalegn Ejigu; Minaleshewa Atlabachew; Eshete Dejen; Gashaw Tilahun (Sustainable Environment)
The effects of pesticides are largely a function of toxicity, exposure time, dose rate and its persistence in the environment. Previous studies conducted in the study area mainly focused on the knowledge, attitude and practices of farmers against implementation of pesticide safety instructions during application and storing the pesticides. Hence, the objectives of the present study were to assess the pesticides applied on crops per a cropping season; the pesticide application practices of farmers and the health risks of pesticide residues on humans and the ecosystems. Quantitative data were collected using a questionnaire and analyzed using descriptive statistics, and qualitative data were grouped and summarized. The findings of the study confirmed that crops were sprayed with pesticides up to 26 times per a cropping season. A hectare of farmland might be sprayed more than 14 kg and 28 kg of pesticides per a cropping season and per a year. In addition to solid formulations, farmers used more than four liters of pesticides per crop per hectare. Farmers sprayed highly toxic pesticides without following the safety instructions and supplied the sprayed crops without waiting for the post-spray time interval. Most pesticides used in the district are in the lists of highly hazardous pesticides and are highly toxic to aquatic organisms including fish. There were also practices of fishing using pesticides in rivers of Fogera District and symptoms of surface water pollution used for drinking. Hence, pesticide residues might be one of the major health risks for farmworkers, consumers and ecosystems of the District. Therefore, monitoring the pesticide supply chain starting from suppliers to end users, continuous ecosystem assessment and food safety monitoring using GC-MS are needed to minimize the effects of pesticide residues on human health and the ecosystems.